Contemporary problems in managing production and services supporting manufacturing processes - (:unkn) unknown (Wydawnictwo Politechniki Łódzkiej, 2009)
[...] The topics in the monograph include the problems of theory and practice of production and service management in specific areas. The first area refers to modern methods of industrial engineering, managing production processes, taking under consideration cooperation and method of improvement of ERP system in manufacturing. The second area is devoted to the question of planning in production enterprises and structural solutions of manufacturing - this area is closed by the problem of the use of ABC method (Activity Based Costing). Yet another, the third, area includes the issues in various approaches to outsourcing. The fourth area refers to Total Productive Maintenance (TPM) and technical objects maintenance. The closing issues in the area are maintenance strategies. The final, fifth, area deals with designing development of a new product, critical analysis of production capacity, challenges in logistics, motivation system and aspects of logistic strategy.[...]

[...] Tematyka monografii obejmuje zagadnienia teorii i praktyki zarządzania produkcją i usługami w określonych obszarach. Pierwszy obszar dotyczy współczesnych metod inżynierii przemysłowej, zarządzania procesami produkcyjnymi z uwzględnieniem kooperacji, metody doskonalenia systemu ERP w wytwarzaniu. Drugi obszar poświęcony zostal zagadnieniu planowania w przedsiębiorstwach produkcyjnych oraz rozwiązań strukturalnych wytwarzania - obszar ten kończy zagadnienie wykorzystania metody ABC (Activity Based Costing). Kolejny trzeci obszar zawiera zagadnienia w różnym ujęciu outsourcingu. Czwarty obszar dotyczy zagadnień utrzymania ruchu (TPM) oraz gospodarki naprawczej (maintenance) obiektów technicznych. Obszar ten kończy zagadnienie strategii naprawczych (maintenence strategies). Ostatni obszar piąty, poświęcony został projektowaniu rozwoju nowego produktu, krytycznej analizie wydajności produkcji , wyzwaniom logistyki, systemowi motywacji i aspektom strategii logistycznej.[...]
Editor in Chief : Wodziński, Piotr
Scientific Editor of the Division : Lewandowski, Jerzy
Keywords: produkcja - zarządzanie; procesy produkcyjne - zarządzanie; przedsiębiorstwo produkcyjne; strategie naprawcze; production - management; production processes - management; manufacturing company; repair strategies